Pandemic Catholic Learning Model at Junior High School in Landak Regency West Kalimantan - Magdalena Magdalena (IJECA (International Journal of Education and Curriculum Application), 2021)
The impact of the Covid-19 "attack" in Indonesia has changed many things, one of which is in terms of teaching. The Catholic religion is no exception. Catholic Religion teachers have shifted the learning model from face-to-face to online (online) with the aim of reducing the frequency of students' physical encounters. These actions have proven to have helped slow the spread of this virus. At first, it was not easy to switch the face-to-face learning mode to online learning, but now it has become a habit. Methods This research is qualitative which was conducted for three months. Field findings were obtained. There are a number of obstacles that must be faced by both teachers and students, especially related to internet networks, laptops, and cellphones. In terms of teaching, the author focuses on two things that are typical of online learning strategies that must be met. First, students follow the learning process as is usually done in class with any strategy, Second, after one or several main teaching materials are completed, students take a learning outcome test to determine whether the student in question has completed it or not. Students who have not achieved completeness are required to take part in the diagnosis-remediation activity. This activity is widely practiced wrongly. An important finding from this research is that the learning model during the Covid-19 period is assignments and visits to students' homes. It turns out that teachers do not always provide material resumes and are accompanied by independent assignments to students based on the material in the textbook according to the Learning Implementation Plan (RPP). Teachers also cannot use WhatsApp media and printouts of teaching material resumes because of difficulties in accessing the internet and not all students have cellphones. It was also found that the teacher visited students' homes. This is done for the sake of justice in obtaining the same knowledge.